HOPE THIS HELPS!! Step 1- Simplifying 8m + 14 + -12 + 4n = 0 Step 2- Reorder the terms: 14 + -12 + 8m + 4n = 0 Step 3- Combine like terms: 14 + -12 = 2 2 + 8m + 4n = 0 Solving 2 + 8m + 4n = 0 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Step 4- Add '-2' to each side of the equation. 2 + 8m + -2 + 4n = 0 + -2 Step 5- Reorder the terms: 2 + -2 + 8m + 4n = 0 + -2 Step 6- Combine like terms: 2 + -2 = 0 0 + 8m + 4n = 0 + -2 8m + 4n = 0 + -2 Combine like terms: 0 + -2 = -2 8m + 4n = -2 Step 7- Add '-4n' to each side of the equation. 8m + 4n + -4n = -2 + -4n Step 8- Combine like terms: 4n + -4n = 0 8m + 0 = -2 + -4n 8m = -2 + -4n Step 9- Divide each side by '8'. m = -0.25 + -0.5n Step 10- Simplifying m = -0.25 + -0.5n

(1) Answers

Add answer

Sign in
Sign up